Bancassurance - współpraca banków i firm ubezpieczeniowych - Kociemska-Pociecha, Hanna (Bancassurance Co-Operation Between Banks and Insurance Companies, 2005)
The banking services are still being developed thanks to the great technological development and globalization of the financial markets. One of the most striking developments in financial services over the past years has been the increasing connections between banks and insurance companies. Most banks now offer insurance products while a substantial number of insurance companies have moved towards offering financial products. This trend is called bancassurance. All over the world banks merge with insurance companies and so arise new financial groups. It emerges that the cooperation between those institutions brings to advantages both of them.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 251-257